Combined Effectiveness of Static Stretching With and Without Post-Isometric Relaxation (PIR) in Managing Pain, Range of Motion and Functional Status Among Upper Cross Syndrome Patients: Combined Effectiveness of Static Stretching - Mudassar, Palwasha; Butt, Zara; Salik, Sumbal; Munawar, Raheel; Hamid, Khizra; Yaseen, Iqra; Saeed, Arslan; Khalid, Amna (Pakistan Journal of Health Sciences, 2023)
Tightness of cervical muscles especially upper trapezius and levator scapulae leads to the limitation of cervical ranges and develop a painful condition named as Upper cross syndrome. Objective: The aim was to determine the effect of Static Stretching along with and without Post Isometric Relaxation (PIR) in managing pain, ranges and disability among the patient with Upper Cross Syndrome. Methods: A hospital-based study was carried out following convenience sampling. Study included 22 patients of 18-50 years suffering with Upper Cross Syndrome divided into two groups. Group A (n=11) managed by Post Isometric Relaxation with Group B (n=11) through Static Stretching. Visual Analogue scale (VAS), Neck Disability Index (NDI) and Goniometer were used for assessment of outcomes. The data was analyzed by suing SPSS version 25.0 in which within and between group analysis were done by using parametric test with p-value< 0.05. Results: The results showed VAS and NDI were significantly improved by PIR with 2.27± 1.27 and SS was 4.00± 1.94 and post-NDI value was 24.90±2.21 and 25.09± 2.84 respectively. Similarly; the post ranges of PIR showed statistically significant results in improving cervical ranges as compared to Static stretching with p-value <0.05 Conclusions: The study concluded that combination of Static Stretching and PIR is significantly effective in improving pain, ranges and functional status among Upper cross Syndrome patient along with rapid recovery rate having p-value <0.05.